FEATURES OF SPIRITUAL AND PHYSICAL EDUCATION OF YOUTH IN EDUCATIONAL INSTITUTIONS - Usmanov Mansur (Bright Mind Publishing, 2025)
This article analyzes the process of spiritual and physical education of young people in educational institutions, its specific features, and its significance. The interrelation between spiritual and physical education in the comprehensive development of the younger generation and its impact on personal growth is highlighted. Additionally, advanced experiences and innovative approaches for effectively organizing this process in educational institutions are recommended.
Keywords: Spiritual education, physical education, educational institutions, youth, personal development, innovative approaches, educational process, comprehensive development.